2006
DOI: 10.1001/jama.296.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Salpingo-oophorectomy and the Risk of Ovarian, Fallopian Tube, and Peritoneal Cancers in Women With a <EMPH TYPE="ITAL">BRCA1</EMPH> or <EMPH TYPE="ITAL">BRCA2</EMPH> Mutation

Abstract: Oophorectomy is associated with reduced risk of ovarian and fallopian tube cancer in high-risk women, although there is a substantial residual risk for peritoneal cancer in BRCA1 and BRCA2 mutation carriers following prophylactic salpingo-oophorectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
298
2
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(329 citation statements)
references
References 25 publications
7
298
2
11
Order By: Relevance
“…Логично, что проведение аднексэктомии приводит к доказанному снижению частоты серозных злокаче-ственных опухолей таза [30]. Можно ли отнести этот же эффект к тубэктомии без удаления яичников?…”
Section: Discussionunclassified
“…Логично, что проведение аднексэктомии приводит к доказанному снижению частоты серозных злокаче-ственных опухолей таза [30]. Можно ли отнести этот же эффект к тубэктомии без удаления яичников?…”
Section: Discussionunclassified
“…Логично, что проведение аднексэктомии приво-дит к доказанному снижению частоты серозных зло-качественных опухолей таза [30]. Можно ли отнести этот же эффект к тубэктомии без удаления яични-ков?…”
Section: Discussionunclassified
“…Premalignant dysplasias within the fallopian tubes have also been linked to BRCA gene mutations. The prevalence of BRCA mutations in the general population ranges between 0.07 and 0.24% for BRCA-1 and 0.14 and 0.22% for BRCA-2 (1). Genetic counseling and risk-reducing surgery, including prophylactic bilateral salpingo-oophorectomy and mastectomy, are often recommended in BRCA carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The median survival rates vary from 11.3 to 17.8 months (5). Prophylactic salpingo-oophorectomy is used for cancer risk reduction in BRCA gene carriers and leads to decrease of ovarian/tubal/peritoneal cancer risk to 3.5-4.3% and breast cancer risk to 30-40% (1,6). In a more optimistic study, prophylactic salpingo-oophorectomy was shown to be more effective in preventing ovarian, tubal, and breast cancers, with low surgical morbidity and complications including hematomas, cardiac arrhythmias, and injury of adjacent organs such as the bladder, ureters, and intestines (4).…”
Section: Introductionmentioning
confidence: 99%